2008
DOI: 10.1002/ejoc.200800030
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Reactions of Trifluorovinylsilanes with Aromatic Aldehydes

Abstract: The conditions for the selective addition of trialkyl(trifluorovinyl)silanes to the C=O bond of aromatic aldehydes in the presence of cesium fluoride to give the corresponding "silylated" alcohols in high yields was performed. The reactivity of the "silylated" alcohols in the presence of nucleophilic reagents and Brönsted acids was studied. On the basis of isolated compounds and of intermediates detected by NMR spectroscopic methods, several reaction pathways are proposed. Significant differences between the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…As a result of this approach, we were able not only to open access to numerous perfluoroalkyl elementates [7] but, in the course of perfluoroalkylation of organic substrates containing multiple bonds (C=C, C=O, C=S and C=N), we were able to obtain stable salts of fluorinated organic anions which were valuable synthons in further and previously impossible transformations. [8][9][10][11][12][13][14] Herein, we report a new and convenient synthetic method for preparing the first perfluoroalkyl (CF 3 , C 2 F 5 ) and trifluorovinyl-containing Fischer carbene complexes on the basis of reactions of tungsten and chromium hexacarbonyls with perfluoroalkyl and trifluorovinylsilanes in the presence of stoichiometric amounts of fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this approach, we were able not only to open access to numerous perfluoroalkyl elementates [7] but, in the course of perfluoroalkylation of organic substrates containing multiple bonds (C=C, C=O, C=S and C=N), we were able to obtain stable salts of fluorinated organic anions which were valuable synthons in further and previously impossible transformations. [8][9][10][11][12][13][14] Herein, we report a new and convenient synthetic method for preparing the first perfluoroalkyl (CF 3 , C 2 F 5 ) and trifluorovinyl-containing Fischer carbene complexes on the basis of reactions of tungsten and chromium hexacarbonyls with perfluoroalkyl and trifluorovinylsilanes in the presence of stoichiometric amounts of fluoride ions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that aromatic aldehydes react with trialkyl(trifluorovinyl)silanes in the presence of fluoride ions to form ''silylated'' trifluoroallylic alcohols. Furthermore, on the basis of the isolated products, we proposed a reaction scheme for the transformation of ''silylated'' alcohols under the influence of nucleophilic agents and Brö nsted acids [7].…”
Section: Introductionmentioning
confidence: 99%
“…This prompted us to develop new and efficient transformations into synthetically useful intermediates. Among a variety of materials, our attention was focused on b-substituted a-fluoro-a,b-unsaturated carboxylic acids 8 [3,4] because of their utility as constituents of biologically active substances.…”
Section: Introductionmentioning
confidence: 99%
“…The vinylic proton of 3 a was further abstracted and the resultant anion could be eventually trapped with appropriate carbonyl compounds to give fluorinated allylic alcohols. [4,7] Intramolecular interaction of Li···F (206.0 pm) in 2 a seemed to be one of the major promoters for conversion to 3 a, which, as a result, would effect a 9.4 pm elongation of the C À F···Li bond. Although 1 b energetically preferred transformation to lithiated 2 b rather than 3 b (by 4 kcal mol À1 on the basis of the present calculation, either in Et 2 O or THF), 2 b is in fact known to follow Keywords: allylic alcohols · carboxylic acids · fluorine · hydrochlorofluorocarbons (HCFCs) · sigmatropic rearrangement Abstract: b-Substituted a-fluoro-a,b-unsaturated carboxylic acids have been successfully synthesized, usually in a (Z)-stereospecific manner by way of a stepwise or a one-pot three-step procedure starting from 2-chloro-1,1,1,2-tetrafluoroethane (HCFC-124), one of the major byproducts of the industrial process for tetrafluoroethene formation from chlorofluoromethane (HCFC-22).…”
mentioning
confidence: 98%